Major issues of organizational and economic mechanisms of migration regulation in Kazakhstan - Mussina, S.T.; Khusainova, Zh.S.; Vechkinzova, Y.A.; Sartova, R.B.; Zhansagimova, A.Y. (KU Publ., 2022)
Object: To identify the current issues of regulating migration processes in Kazakhstan with an emphasis on external migration. Methods: Information systematization, working with sources, methods of studying cause-and-effect relationships. Findings: Based on the analysis of trends in the development of migration processes in Kazakhstan, we have explored the main policy directions of their regulation. We have studied the institutional model of regulation of migration processes in Kazakhstan, raised the issues of interdepartmental interaction of various bodies in the implementation of migration policy in our country. We have investigated the factors affecting the establishment of the agenda in migration regulation for authorized bodies. We have studied the problem of unregulated migration in Kazakhstan, given a description of the risks associated with it, and presented proposals for improving measures to regulate migration processes. Conclusions: Regulation of external migration processes in Kazakhstan is currently connected with the issues of adaptation and integration of ethnic repatriates in the Republic of Kazakhstan, reducing the negative impact of emigration outflow in the northern and north-eastern, and central regions of the Republic of Kazakhstan (depopulation, staff shortage, reduction of the development potential of rural settlements, etc.). Measures are required to increase the demographic potential of regions with an intensive external population outflow, to stimulate immigration to Kazakhstan, to create conditions for the successful integration of ethnic repatriates in the host society, to reduce illegal labor migration, to curb educational migration (or at least, to reduce the risks of its transition into non-returnable emigration.
Қазақстандағы көші-қонды реттеудің ұйымдастырушылық-экономикалық тетіктерінің өзекті мәселелері
Актуальные вопросы организационно-экономических механизмов миграционного регулирования в Казахстане
Keywords: migration; Kazakhstan; external migration; unregulated migration; migration policy; labor migration; educational migration